Prevalence, Predictors, and Disease Activity of Sacroiliitis Among Patients with Crohn's Disease. Issue 6 (14th August 2020) - Levine, Irving; Malik, Fardina; Castillo, Gabriel; Jaros, Brian; Alaia, Erin; Ream, Justin; Scher, Jose U; Hudesman, David; Axelrad, Jordan
Abstract: Background: Sacroiliitis is an inflammatory arthritis of the sacroiliac joints and is associated with inflammatory bowel disease (IBD). Yet, sacroiliitis often goes undiagnosed in IBD, and the clinical association between IBD disease activity and sacroiliitis is not well established. Patients with Crohn's disease (CD) often receive magnetic resonance enterography (MRE) to assess disease activity, affording clinicians the opportunity to evaluate for the presence of sacroiliitis. We aimed to identify the prevalence and disease characteristics associated with sacroiliitis in CD patients undergoing MRE. Methods: All CD patients undergoing MRE for any indication between 2014 and 2018 at an IBD referral center were identified. The MREs were reviewed for the presence of sacroiliitis based on bone marrow edema (BME) and structural lesions. We analyzed demographics, IBD characteristics, clinical and endoscopic disease activity, and management between CD patients with and without sacroiliitis. Results: Two hundred fifty-eight patients with CD underwent MRE during the study period. Overall, 17% of patients had MR evidence of sacroiliitis, of whom 73% demonstrated bone marrow edema. Female gender, back pain, and later age of CD diagnosis were associated with sacroiliitis ( P = 0.05, P < 0.001, P = 0.04, respectively). Disease location and CD therapy were not associated with sacroiliitis on MRE. Clinical, endoscopic, and radiographic disease activity were not associated with sacroiliitis on MRE. Conclusion: Sacroiliitis is a common comorbid condition in CD. With limited clinical clues and disease characteristics to suggest sacroiliitis, physicians may utilize MRE to identify sacroiliitis, especially in CD patients with back pain.